A subset of yeast vacuolar protein sorting mutants is blocked in one branch of the exocytic pathway - Harsay, Edina (The Rockefeller University Press, 2002)
Exocytic vesicles that accumulate in a temperature-sensitive sec6 mutant at a restrictive temperature can be separated into at least two populations with different buoyant densities and unique cargo molecules. Using a sec6 mutant background to isolate vesicles, we have found that vacuolar protein sorting mutants that block an endosome-mediated route to the vacuole, including vps1, pep12, vps4, and a temperature-sensitive clathrin mutant, missort cargo normally transported by dense exocytic vesicles, such as invertase, into light exocytic vesicles, whereas transport of cargo specific to the light exocytic vesicles appears unaffected. Immunoisolation experiments confirm that missorting, rather than a changed property of the normally dense vesicles, is responsible for the altered density gradient fractionation profile. The vps41Δ and apl6Δ mutants, which block transport of only the subset of vacuolar proteins that bypasses endosomes, sort exocytic cargo normally. Furthermore, a vps10Δ sec6 mutant, which lacks the sorting receptor for carboxypeptidase Y (CPY), accumulates both invertase and CPY in dense vesicles. These results suggest that at least one branch of the yeast exocytic pathway transits through endosomes before reaching the cell surface. Consistent with this possibility, we show that immunoisolated clathrin-coated vesicles contain invertase.